Emotional intelligence and occupational performance among Malaysian librarians - Masrek, Mohamad Noorman; Abdullah Sani, Mad Khir Johari; Jamaludin, Adnan (2012)
Today, the skill of emotional intelligence (EI) has become very popular and is being adopted into the standard set of management skills. By definition, EI is the ability to identify, assess, and control the emotions of oneself, of others, and of groups. It has been shown in numerous studies that EI skills are essential in determining not only employee job commitment and job satisfaction, but also job performance. Realizing the importance and contribution of EI towards job performance, many public and private organizations have started to include EI as one of the skills that need to be acquired and exercised by their employees when delivering their jobs. The Government of Malaysia, for instance, had developed various policies that stressed the importance of exercising EI among its employees. These policies which include Bersih, Cekap dan Amanah; Penerapan Nilai-nilai Islam; Islam Hadhari and Pencapaian diutamakan, Rakyat Didahulukan entail various EI skills that need to be exercised by all government staffs when executing their jobs. Mining the literature on EI studies suggest that researchers have developed various theoretical models and framework for measuring EI. Most of these models and frameworks have been empirically tested in diverse job setting which includes teachers, lecturers, doctors, administrators, engineers and salesman. One of the most popular and successful models for measuring EI is the one developed by Goleman (1995). The model consists of 16 variable grouped into four dimensions namely, self awareness, self management, social awareness and relationship management. Apart from being used by numerous researchers for studying and measuring EI, the model is also being used in the training curriculum on improving EI skills. Goleman (1995) identified various professions that require extensive skills of EI which include librarian. Interestingly, while many of the listed professions have been studied by researchers in terms of their EI level, none has ever attempted to validate the Goleman's model among librarians. Given this background, this study attempts to adapt the Goleman's model and develop and EI model that is specifically suited for the